2016
DOI: 10.1080/13603116.2016.1197324
|View full text |Cite
|
Sign up to set email alerts
|

Students with autism transitioning from primary to secondary schools: parents’ perspectives and experiences

Abstract: The transition from primary to high school can be a challenging process for students with autism spectrum disorder (ASD). During this time, researchbased practices like home-school collaboration are crucial in facilitating a smoother transition. However, existing research indicates that the transition from primary to high school is a period of anxiety and reduced support for students with ASD and their families. This article describes the experiences of parents of students with ASD in regard to this transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 43 publications
(56 reference statements)
1
27
0
1
Order By: Relevance
“… prediction of adjustment after the move (Kingery et al , ; Waters et al , ) enhanced resilience (Hammond, ) and Tso and Strnadova () attitudes to school and teacher (Symonds & Hargreaves, ) robust relationship between peer acceptance and academic [Kingery et al , ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… prediction of adjustment after the move (Kingery et al , ; Waters et al , ) enhanced resilience (Hammond, ) and Tso and Strnadova () attitudes to school and teacher (Symonds & Hargreaves, ) robust relationship between peer acceptance and academic [Kingery et al , ) …”
Section: Resultsmentioning
confidence: 99%
“…Other important influences reported in the research were peer acceptance, with both the number and quality of friendships prior to leaving primary school being reported as making substantial contributions to the predicted positive or negative adjustments after the move (Kingery et al , ; Waters et al , ). Positive peer relationships acted as a protective factor to cope with challenges related to the move (Kingery et al , ; Hammond, ; Symonds & Hargreaves, ; Tso & Strnadova, ), and there was evidence that they contributed to academic achievement (Kingery et al , ). However, Langenkamp () found that for most pupils, social relationships in primary school protected them against negative educational outcomes after the move to secondary school, but not for lower achieving primary school pupils.…”
Section: Resultsmentioning
confidence: 99%
“…At the time of conducting this research, only nine studies had focused on the primary to secondary school transition of young people with ASC, all but one originating from the UK (the exception being Australia in Tso & Strnadova, ). Samples sizes vary but tend to be relatively small (average number 12, with a range of 5–28), with qualitative methodologies more frequently employed.…”
Section: Introductionmentioning
confidence: 99%
“…This in-between educational arrangement might increase the dependency on well-developed strategies for communication and planning among the teacher in charge of adapted and general PE. Based on previous research, we see that these educational transitions are often perceived as particularly challenging in terms of communication, planning, and support (Tso and Strnadová 2017;Wilhelmsen and Sørensen 2018).…”
Section: Interaction Between Child Intrapersonal Characteristics and mentioning
confidence: 87%